No increased risk of psoriasis in patients receiving androgen deprivation therapy for prostate cancer: a 17-year population-based study - Liu JM; Lin CY; Chuang HC; Hsu RJ (Dove Medical Press, 2018)
Jui-Ming Liu,1–3,* Chien-Yu Lin,4,* Heng-Chang Chuang,1 Ren-Jun Hsu3,5,6 1Division of Urology, Department of Surgery, Taoyuan General Hospital, Ministry of Health and Welfare, Taoyuan, Taiwan; 2Department of Medicine, National Yang-Ming University, Taipei, Taiwan; 3Graduate Institute of Life Sciences, National Defense Medical Center, Taipei, Taiwan; 4Department of Pediatrics, Hsinchu MacKay Memorial Hospital, Hsinchu, Taiwan; 5Biobank Management Center of the Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan; 6Department of Pathology and Graduate Institute of Pathology and Parasitology, the Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan *These authors contributed equally to this work Objective: Androgen deprivation therapy (ADT) use in prostate cancer (PCa) patients has been reported to exacerbate the course of psoriasis. We aimed to assess the impact of ADT on the subsequent risk of psoriasis. Methods: We utilized data from the National Health Insurance Research Database of Taiwan between 1996 and 2013. In total, 17,168 patients with PCa were identified; 5,141 ADT patients comprised the study group with 5,141 matched non-ADT controls. We used 1:1 propensity score-matched analysis. The demographic characteristics and comorbidities of the patients were analyzed; Cox proportional hazards regression was used to calculate the HRs for the risk of psoriasis. Results: Eighty-nine (0.87%) patients with newly diagnosed psoriasis were identified. Compared with non-ADT patients, ADT patients had similar risk of subsequent psoriasis with an HR of 0.95 (95% CI 0.63–1.45; P=0.816). However, a higher risk of psoriasis was observed in angiotensin-converting enzyme inhibitors patients (adjusted HR 2.14, 95% CI 1.09–4.20; P<0.05). Conclusion: ADT use did not increase risk of psoriasis in patients with PCa. Further studies are warranted to assess the clinical significance. Keywords: prostate cancer, psoriasis, androgen deprivation therapy